DETERMINATION OF THE STABILITY CONSTANTS OF THE PROTON AND Co(II), Ni(II), Cu(II), Zn(II), Fe(III) COMPLEXES OF 3,5-DIMETHYL TETRAHYDRO-1,3,5-THIADIAZINE-2-THIONE BY THE POTENTIOMETRIC METHOD - Ercag, Ayse; Turak, Fatma; Ozgur, Mahmure; Bozdogan, Abdurrezzak (YILDIZ TECHNICAL UNIV, 2007)
Dazomet (DTTT), (tetrahydro-3,5-dimethyl-2H-1,3,5-thiadiazine-2-thione) is soil fumigant used to control weeds, soil fungicide, insects and nematodes. DTTT was synthesized and purified according to literature. The protonation constant of DTTT in water-ethanol 70:30(v%) solution was determined by potentiometric titration at constant temperature, t = (25 +/- 0.1 degrees C) and 0.06 M NaClO4 as ionic background. The formation constants of DTTT with Cu(II), Ni(II), Co(II), Zn(II), and Fe(III) were determined at the same conditions. Purified nitrogen gas bubbled through the titrated solution to ensure stirring and neutral inert atmosphere. Furthermore, the solution was stirred magnetically. The solutions were titrated with 5.10(-3) M NaOH in increments of 0.1 mL. The corresponding change in the pH value of the solution was measured. The stochiometric protonation constants of the ligand were calculated using software called TITFIT developed by Zuberbuhler and Kaden(1). The formation constant of DTTT complexes with Cu(II), Ni(II), Co(II), Zn(II), Fe(III) and species distribution curves were calculated and plotted using TITFIT computer program. The values of the protonation constants for the ligand are log beta(1) = 9.49 (Delta=2.36.10(-2)) and log beta(2)- 13.50 (Delta=2.38.10(-2)). The order of the stability constants of ML complexes with DTTT is Fe>Cu>Co>Ni>Zn and that of MLH complexes is Co>Cu>Fe>Ni>Zn.
Keywords: Dazomet; pesticide; stabilite constants; potentiometric method; TITFIT programme; Engineering